An integrated marketing communications campaign for Globe GCash beep MasterCard - Lunod, Aldrin I. (Animo Repository, 2016)
On third quarter (3rd) quarter of 2015, G-Xchange, Inc., a subsidiary of Globe Telecom launched the Globe GCash beep MasterCard, a reloadable prepaid card positioned as an Everyday-all-in-one card. The Card can be used for bills payment, buy prepaid load at a discounted price, online shopping and cash withdrawals from any ATM bank machines with MasterCard affiliation/accreditation. The beep feature allows the cardholder to pay for the MRT/LRT fare. The Globe GCash beep MasterCard is meant to target the younger segment age 18-35 years old that are college student or working professional. The target audience is a user of debit card due to no monthly billings and annual membership fee. The respondents are heavy Internet users and own at least one (1) unit of mobile phone. Brand awareness and increase card acquisition are the two (2) main objectives of the campaign to be able to rise against the clutter of three (3) competitor brands in the category: PayMaya Visa beep Card, Smart Money MasterCard, and Yazz Visa beep Card. To reach on the target audience, the following contact points were used: Digital Media such as social media, Search Engine Optimization (SE0) and Banner Ads. Furthermore, Below-the-Line (BTL) such as brand activations through bazaars and school fairs in different areas of Metro Manila were also utilized.